Bromodimethylsulfonium Bromide (BDMS)-Catalyzed Synthesis of 1,5-Benzodiazepines Using a Multi-Component Reaction Strategy - Sarkar, Satavisha; Deka, Jugal Kishore Rai; Hazra, Jagadish P.; Khan, Abu T. (Synlett, 2013)
A new approach for the synthesis of multi-functionalized 1,5-benzodiazepines is developed starting from o-phenylenediamines, β-keto esters and aromatic aldehydes utilizing a one-pot, three-component strategy employing bromodimethylsulfonium bromide as the catalyst. The simple reaction procedure, good yields, mild reaction conditions and applicability to a wide range of substrates are some of the salient features of this protocol.
Keywords: multi-component reactions; 1,5-benzodiazepines; o-phenylenediamines; bromodimethylsulfonium bromide